The Effectiveness of Using Communicative Language Teaching (CLT) on Speaking Ability at Seventh Grade of SMP Miftahul Ulum Jember - Dwi Nur Hadiyansah WS; Nuril Qomariyah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The purpose of the research was to find out the effectiveness of using communicative language teaching on speaking ability in SMP Miftahul Ulum Jember. This research used a quantitative method. The research applied pre-experimental research with one group pre-test and post-test design. The population of this research was the seventh-year students of SMP Miftahul Ulum Jember in academic 2023-2024. The sample consisted of 20 students of class VII. The data were collected through speaking test (pre-test and post-test). To find out the effectiveness of communicative language teaching (CLT) on speaking ability, the researcher applied t-test analysis. The research was held in three meetings.The findings indicated that there was a significant difference between pre-test and post-test. The result the t-test result sig. 0.000 < 0.005, so Ho was rejected and Ha was accepted. It can be seen the value of t-test tcount 4635 > ttable 2.093 than t-test (0.00) and degree of freedom (df)= 19. Therefore, the researcher concluded that the use of communicative language teaching (CLT) approach was effective on the student’s speaking ability.